THE OPTIMIZATION OF MULTIPURPOSE BUILDING DEVELOPMENT ON PROJECT SCHEDULING USING PRECEDENCE DIAGRAM METHOD (PDM) - Sutrisno Sutrisno; Ahmadi Ahmadi; Okol S Suharyo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2018)
ABSTRACT The current development of construction projects lead to construction projects being more complex and complicated. The success or failure of a project can be due to inadequate planning and less effective controls, resulting in inefficient projects. This will result in delays, lower quality, and increased implementation costs. All of those problems are expected to be overcome with Presedence diagram method by reducing the impact of delay and swelling of project cost by crashing with applied overtime. Acceleration of duration on the critical path jobs was performed. The results with PDM indicated that the optimal duration of project was 100 days with efficiency time for 20 days or equal to 16,67% and the total cost of Rp 13,060,754,232.00 with cost efficiency equal to Rp 528,158,094.00 or 3,88%. Keywords: Crashing, Controlling, Planning, PDM